Li3V2(PO4)3 encapsulated flexible free-standing nanofabric cathodes for fast charging and long life-cycle lithium-ion batteries. Issue 14 (18th March 2016) - Sun, Pingping; Zhao, Xueying; Chen, Renpeng; Chen, Tao; Ma, Lianbo; Fan, Qi; Lu, Hongling; Hu, Yi; Tie, Zuoxiu; Jin, Zhong; Xu, Qingyu; Liu, Jie
Abstract : Lithiated transition metal phosphates with large theoretical capacities have emerged as promising cathode materials for rechargeable lithium-ion batteries. Abstract : Lithiated transition metal phosphates with large theoretical capacities have emerged as promising cathode materials for rechargeable lithium-ion batteries. However, the poor kinetic properties caused by their low intrinsic electronic and ionic conductivity greatly hinder their practical applications. In this work, we demonstrate a novel strategy to prepare monoclinic lithium vanadium phosphate nanoparticles implanted in carbon nanofibers as the cathodes of Li-ion cells with high capacity, flexibility, long cycle stability and significantly improved high-rate performance. The composite nanofibers were obtained by electrospinning using polyacrylonitrile and Li3 V2 (PO4 )3 nanoparticles, followed by annealing and coating with a thin layer of carbon by plasma enhanced chemical vapor deposition. The Li3 V2 (PO4 )3 nanocrystals with the monoclinic phase were uniformly distributed in the composite nanofibers. The electrochemical performances of the as-prepared binder-free fibrous cathodes were characterized by potentiostatic and galvanostatic tests. At the rate of 0.5 C in the range of 3.0–4.3 V, the composite displayed an initial discharge capacity of 128 mA h g −1 (96.2% of the theoretical capacity). A discharge capacity of 120 mA h g −1 was observed even at a high rate of 10 C, and a capacity retention of 98.9% was maintained after 500 cycles at 5 C, indicating excellent high-rate capability and capacity retention. Compared to the control samples without a carbon outer-layer, the composite nanofibers with carbon coating demonstrated much better electrochemical performances. It indicates that the carbon coating can further protect the structural integrity of nanofabric electrodes during the charge/discharge processes without hindering the Li-ion mobility and also can prevent undesired side reactions with an electrolyte, thus greatly improving the rate performance and cyclic stability of the cathode.